COVID-19 Preventive Behaviors and Influencing Factors in the Thai Population: A Web-Based Survey - Rojpaisarnkit, Kunwadee; Kaewpan, Wonpen; Pengpid, Supa; Peltzer, Karl (Frontiers in Public Health, 2022)
Objectives: To identify factors influencing COVID-19 preventive behaviors among Thai population. Methods: A cross-sectional web-based survey was used. A total of 6,521 Thai people completed the survey. The multiple linear regression analysis was performed to identify factors that influenced COVID-19 preventive behaviors. The PRECEDE model was applied to propose factors influencing COVID-19 preventive behaviors. Results: Factor most influencing COVID-19 prevention behaviors when controlling for the other variables was social support (β = .173, p < .001) follow by age (β = .162, p < .001 ), flu like symptoms (β = .130, p < .001), gender (β = -.084, p < .001), perceived risk of exposure (β = .035, p < .05), lock down policy (β = .029, p < .05), and residential area (β = -.027, p < .05), respectively. These factors explained 52% of the COVID-19 preventive behaviors in Thai population. Conclusion: The results of this study was a foundation for further studies in different groups of people in order to develop different strategies to adopt preventive behaviors to reduce spread of COVID-19.